The energy of thermal electrons in electron beam created helium discharges - Yu, Z., author; Collins, G. J., author; Rocca, Jorge J., author; She, C. Y., author; North-Holland, publisher (Colorado State University. Libraries, 1983)
We have measured the electron energy of the thermal group of electrons in both longitudinal and transverse electron beam created helium glow discharges. The measurement technique employs the ratio of intensities of spectral lines in the 2s 3S-np 3P He I series. Values of kTe between 0.07 and 0.11 eV were obtained. These energies are typical of the beam generated electric field free plasmas. The competitive loss of helium ions by recombination and by charge transfer in a He-Hg electron beam created plasma is calculated. The results are applied to the Hg+ laser pumping scheme using a electron beam created He-Hg plasma.